2016
DOI: 10.1007/s00269-016-0821-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the attenuated total reflectance infrared (ATR-FTIR) spectrum of apatite

Abstract: . Modeling the attenuated total reflectance infrared (ATR-FTIR) spectrum of apatite. Physics and Chemistry of Minerals, Springer Verlag, 2016, 43 (9) 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 55 publications
5
42
0
Order By: Relevance
“…The ATR spectra of these two samples are about four times more intense than those recorded on the collagen-rich bone samples. As previously observed by Aufort et al (2016), significant differences are observed between the spectra recorded using a Ge or a diamond crystal for the whole series of samples. Beside a stronger intensity, the intense n 3 stretching and n 4 bending PO 4 bands of the diamond-ATR spectra are broadened on their low-frequency side, and the n 3 band overlaps with the weaker n 1 PO 4 and n 2 CO 3 bands.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…The ATR spectra of these two samples are about four times more intense than those recorded on the collagen-rich bone samples. As previously observed by Aufort et al (2016), significant differences are observed between the spectra recorded using a Ge or a diamond crystal for the whole series of samples. Beside a stronger intensity, the intense n 3 stretching and n 4 bending PO 4 bands of the diamond-ATR spectra are broadened on their low-frequency side, and the n 3 band overlaps with the weaker n 1 PO 4 and n 2 CO 3 bands.…”
Section: Introductionsupporting
confidence: 62%
“…However, the theoretical spectra of collagen-rich samples overestimate the intensity of their experimental counterparts, which are about four times less intense than those of collagen-poor samples (e.g., for modern ox bone the theoretical intensities require a 0.175 scale factor to match the experimental ones). As discussed in Aufort et al (2016), this theoretical overestimation is most likely related to sample heterogeneities, but further grinding of the collagen-rich samples did not allow recovering the theoretical intensities. Note that a decrease in the mineral fraction modifies the line shape (Supplemental Information) and cannot account for a simple decrease of the whole spectrum intensity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations